A novel INS mutation in a family with maturity‐onset diabetes of the young: Variable insulin secretion and putative mechanisms. Issue 5 (22nd May 2018) - Johnson, Stephanie R; McGown, Ivan; Oppermann, Udo; Conwell, Louise S; Harris, Mark; Duncan, Emma L
Abstract : Insulin gene ( INS ) mutations cause a rare form of maturity‐onset diabetes of the young (MODY), a heterogeneous group of autosomal dominant diabetes with at least 14 confirmed causative genes. Here, we describe a family with MODY due to a novel INS mutation, detected using massively parallel sequencing (MPS). The proband presented aged 11 years with mild diabetic ketoacidosis. She was negative for IA2 and GAD antibodies. She had a strong family history of diabetes affecting both her two siblings and her mother, none of whom had ketosis but who were considered to have type 1 diabetes and managed on insulin, and her maternal grandfather, who was managed for decades on sulfonylureas. Of note, her younger sister had insulin deficiency but an elevated fasting proinsulin:insulin ratio of 76% (ref 5%‐30%). Sanger sequencing of HNF4A, HNF1A, and HNF1B in the proband was negative. Targeted MPS using a custom‐designed amplicon panel sequenced on an Illumina MiSeq detected a heterozygous INS mutation c.277G>A (p.Glu93Lys). Sanger sequencing confirmed the variant segregated with diabetes within the family. Structural analysis of this variant suggested disruption of a critical hydrogen bond between insulin and the insulin receptor; however, the clinical picture in some individuals also suggested abnormal insulin processing and insulin deficiency. This family has a novel INS mutation and demonstrated variable insulin deficiency. MPS represents an efficient method of MODY diagnosis in families with rarer gene mutations.